(untitled) (Research, Society and Development, 2022)
The vertical garden is a gardening method that allows plants to grow suspended from the surface, taking up little space and the mixed garden is a living laboratory available for different didactic activities. When inserted in the school environment, it enables the development of the students’ teaching-learning process, providing them with the opportunity to learn environmental values. The objective of this work was to make a vertical garden through the reuse of recyclable objects, providing a healthier life, and to install a mixed garden where it provides a set of advantages to the school community, such as the approach to themes related to Environmental Education. The project served students with Deafness, Cerebral Palsy, Intellectual Disability, Down Syndrome, aiming for them to be able to intervene in the local reality in order to contribute to the reformulation of thoughts of the authors involved. The implementation of vegetable gardens, vertical and mixed, was implemented from August 2018 to February 2019, at the Nossa Senhora Divina Pastora Elementary School, located in the municipality of Junqueiro - AL. Due to the aforementioned facts, the creation of the vertical garden and the mixed vegetable garden stimulated the motor skills of students with special needs. In which teaching strategies were created for the curricular subjects that involve Environmental Education. Putting into practice the importance of the garden and vegetable garden in the use of recyclable materials, seeking interaction between the students involved, with the environment and plants.